"It is my body, so I decide" A multidisciplinary approach to the interpretation of article 14 of the protocol to the African charter on the rights of women in Africa - Viljoen, Frans (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2011.